2018
DOI: 10.14744/nci.2018.68815
|View full text |Cite
|
Sign up to set email alerts
|

How to get Ethics Committee Approval for Clinical Trials in Turkey?

Abstract: The “ethics committee approval” required to conduct clinical trials can be difficult to obtain for researchers due to problems with their time management, evaluating clinical investigations as a routine process as a part of their work; confusions regarding the concepts of treatment, interference, research and intervention, and sometimes due to lack of knowledge. Ethics committee approval process in our country is discussed by informing the investigators who want to conduct clinical research, about the issues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…In the study conducted by Jones et al, [20] in parallel with this study, it was determined that 56% of the applications made to a hospital ethics committee operating in England between 2008 and 2009 were requested for correction. These data show that researchers need to be informed about the preparation of ethics committee application files [9] . In addition, not allocating enough time for the preparation of application files or being careless can be considered as another reason.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the study conducted by Jones et al, [20] in parallel with this study, it was determined that 56% of the applications made to a hospital ethics committee operating in England between 2008 and 2009 were requested for correction. These data show that researchers need to be informed about the preparation of ethics committee application files [9] . In addition, not allocating enough time for the preparation of application files or being careless can be considered as another reason.…”
Section: Discussionmentioning
confidence: 96%
“…Ethics committees carry out these examinations through the project file prepared by the responsible researchers. The sections that should be included in the relevant file are: project summary, general information, justification for the study, literature review, aim and purpose of the study, methodology, data acquisition and analysis, expected outputs in the study, duration of the project, project management, informed consent form, budget and financing institutions, responsibility sharing and resumes of researchers [9] . A well-designed and fully completed application file provides an overview of the entire proposed work and assists in the review of the work objectively [10,11] , while the review process of incompletely filled application files is timeconsuming and difficult [12,13] .…”
mentioning
confidence: 99%
“…A study related to EC applications for non-invasive studies submitted by a private foundation university found that the percentage of individual study and residency thesis applications was 36.5–45.5% and 5.3–6.9%, respectively. [ 3 ] However, Şişli Hamidiye Etfal is a training and research hospital, and hospitals of this category generally graduate many specialists each year, unlike foundation universities. This could explain the large representation (40.4%) of thesis studies among our applications.…”
Section: Discussionmentioning
confidence: 99%
“…These constitute essential minimum requirements for the evaluation of a research application. [ 3 ] Following this preliminary assessment, the applicants are sent a form advising them of any issues to be revised or corrected. Files resubmitted with the required amendments are re-evaluated by the EC.…”
mentioning
confidence: 99%
“…A study conducted in Germany and Turkey also examined major design issues such as the issue of consent and the problems of complementary medicine research [24,25].…”
Section: Research Design and Questionmentioning
confidence: 99%